Pengaruh Stimulus Lingkungan Toko dan Faktor Lingkungan Sosial terhadap Perilaku Pembelian Impulsif pada Carrefour Sunset Road di Denpasar - Yuliartini, Ni Putu Eka; Sulistyawati, Eka (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
ABSTRACT S tore environment al stimuli is done promotional techniques to increase consumer spending is not planned to certain product groups .Social environmental factors may include employee assistance and employee perceptions. The two variables that influence impulsive buying an entire purchase made without a plan is usually due to the stimulation of interest in Carrefour Sunset Road in Denpasar.The purpose of this study was to determine how significant the effect of environmental stimuli stores and social environmental factors on the behavior of impulse purchases at Carrefour Sunset Road in Denpasar. This study used a questionnaire as data collection techniques were measured using a Likert scale with 11 indicators.In this study using 110 respondents were taken by purposive sampling technique. Analytical methods used are descriptive statistics, which are used to describe the characteristics of respondents and inferential statistics such as multiple regression analysis. The results of this study indicate that environmental stimuli stores and social environmental factors have a significant effect simultaneously on impulsive buying behavior at Carrefour Sunset Road in Denpasar. Keys: Store Environmental Stimuli, Social Environmental Factors, Impulsive Buying Behavior
Keywords: Store Environmental Stimuli, Social Environmental Factors, Impulsive Buying Behavior